Fiscal Policy and Growth in the Context of European Integration - Masson, Paul (IMF Working Papers; Working Paper ;, 2000)
The paper considers the issue of whether a supranational fiscal policy in Europe is needed, and, if so, what responsibilities it should undertake. The literature on endogenous growth and the principle of subsidiarity suggest that such a policy should be limited to externalities or economies of scale not captured at the national level. These may include spending on research and development and transportation or knowledge networks, and harmonization of social security designed to enhance labor mobility. EU-wide stabilization policy or enhanced EU redistribution does not seem justified, however.